The Challenges in Marketing Strategy of âSekar Mayangâ Home Industry - , ANINDA AFG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project aims to identify what is Sekar Mayang and what kind of products that are produced by this home industry. In addition, this paper also aims to explain strategy of marketing applied by Sekar Mayang home industry and how it faces the challenges. These days home industry business has become one of the most desirable types of business for people, so hopefully this article can help and contribute to the readers and especially for all the students at English Program Vocational School in the data collection, in the field of business information. The method of data collection was done by field studies and library study. For the field study, the writer conducted a direct observation on activities in Sekar Mayang. In addition to strengthen the observation, the writer also interviewed Sekar Mayangâs owners and employees. These observations were carried out for 5 months. For the library research to gather background information in the discussion of this paper the writer read some books, read the websites of Sekar Mayang, and some articles from the internet related to the object of research. Based on direct observation and interviews to the owner of Sekar Mayang, the writer obtained some information that Sekar Mayang has several distinct strategies and the challenges strategy in marketing of its products, such as joining the exhibition, expanding the market not only in Jogja, and giving attractive prices comparable to the quality of the product that became the challenges for Sekar Mayang to increase the quality for each products. In addition, the results of how Sekar Mayang face challenges in business marketing strategy shows that Sekar Mayang is very prepared in home-based business industry.